2014
DOI: 10.1121/1.4880856
|View full text |Cite
|
Sign up to set email alerts
|

Personalization of head-related transfer functions in the median plane based on the anthropometry of the listener's pinnae

Abstract: A listener's own head-related transfer functions (HRTFs) are required for accurate three-dimensional sound image control. The HRTFs of other listeners often cause front-back confusion and errors in the perception of vertical angles. However, measuring the HRTFs of all listeners for all directions of a sound source is impractical because the measurement requires a special apparatus and a lot of time. The present study proposes a method for estimating the appropriate HRTFs for an individual listener. The propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The individualization, which is often based on the anthropometric data of humans, requires a basic understanding of the physical effects such as diffraction, refraction and interference on the body. 8 Meanwhile at lower frequencies, the body and head dimensions are of major importance, 7,28 the main influence on higher frequencies is caused by the pinna (see, for example, publications 16,22 ). For a detailed study of the relationship between the HRTF and the anthropometric measures, large databases, providing both, are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The individualization, which is often based on the anthropometric data of humans, requires a basic understanding of the physical effects such as diffraction, refraction and interference on the body. 8 Meanwhile at lower frequencies, the body and head dimensions are of major importance, 7,28 the main influence on higher frequencies is caused by the pinna (see, for example, publications 16,22 ). For a detailed study of the relationship between the HRTF and the anthropometric measures, large databases, providing both, are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with each of those two previous datasets, as a group the participants in the present study showed on average a deeper concha as evaluated by d CIPIC (60% deeper and 13% deeper, respectively), a wider concha as evaluated by W (39% wider and 15% wider, respectively), and a comparable concha height as evaluated by H (7% longer and 1% shorter, respectively). The greater similarity with the pinna measurements of Iida et al (2014) may possibly reflect the common inclusion of mostly Japanese participants, but the small sample sizes preclude any further discussion on racial tendencies in pinna geometry.…”
Section: A Anthropometric Measurementsmentioning
confidence: 91%
“…5 (d CIPIC , W, and H), corresponding pinna anthropometry available in the CIPIC database (Algazi et al, 2001; http:// interface.cipic.ucdavis.edu/sound/hrtf.html) are shown by dots on the left side of our data (respectively, "d 8 ," "d 3 ," and "d 1 "þ"d 2 "), and those listed in Iida et al (2014) are shown by dots on the right side (respectively, "x d ," "x 2 ," and "x 6 "þ"x 7 "). The range, mean, and standard deviation of each of these sets of measurements are listed in Table II.…”
Section: A Anthropometric Measurementsmentioning
confidence: 99%
See 2 more Smart Citations